Adolescents’ HIV Preventive Behavior: The Roles of HIV Literacy, HIV Sensitivity, AI Openness, and Chatbot Engagement - Masruroh Masruroh; Agus Susanto; Heny Noor Wijayanti (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Adolescents remain vulnerable to HIV due to gaps in knowledge, attitudes, and digital health engagement. Cognitive, attitudinal, and digital factors may influence preventive behaviors, yet their combined effects remain underexplored, particularly as adolescents increasingly interact with AI-driven platforms that shape health information access. Objective: This study aimed to examine the associations of HIV literacy, HIV sensitivity, AI openness, and chatbot choice with HIV preventive behaviors among adolescents. Methods: A cross-sectional study was conducted among 910 senior high school and vocational students in Sleman Regency, Indonesia. Participants completed a validated questionnaire assessing HIV preventive behavior (low vs. high) and four predictors: HIV literacy, chatbot choice, AI openness, and HIV sensitivity. Chi-square tests were used to assess bivariate associations. Multivariate logistic regression identified independent predictors, with odds ratios (ORs) and 95% confidence intervals (CIs) reported. Results: Bivariate analyses showed that higher HIV literacy, greater HIV sensitivity, increased AI openness, and active chatbot choice were significantly associated with high-level HIV preventive behavior (all p < 0.001). Multivariate logistic regression confirmed all variables as significant independent predictors: HIV literacy (OR = 1.18, 95% CI: 1.12–1.24), chatbot choice (OR = 1.10, 95% CI: 1.05–1.16), AI openness (OR = 1.08, 95% CI: 1.02–1.14), and HIV sensitivity (OR = 1.10, 95% CI: 1.04–1.16). The model explained a meaningful proportion of variance in preventive behavior (Nagelkerke R² = 0.234). Conclusion: HIV literacy, HIV sensitivity, and engagement with AI-based digital tools significantly predict adolescents’ HIV preventive behaviors. Interventions that enhance knowledge, strengthen attitudes, and promote informed digital decision-making may reinforce HIV prevention efforts among adolescents.